Bertani diantara Himpitan Tambang - Itra Itra; Hasniah Hasniah; Abdul Jalil (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2024)
This research aims to find out the strategy of farmers in overcoming the problem of mining waste. The results of this study show that the Kiaea community who work as farmers are divided into two, namely field farmers and rice farmers. People who work as field farmers, the location of the plantation close to the mine is forced to leave the land because the plants are covered by dust so that they wither and die. Many residents lost their plantation land due to mining. However, they have a way to keep the land profitable, namely that the mine must compensate, both plants and land. In addition, the presence of mining is certainly a place to accommodate labor and open employment opportunities, such as in the process of building buildings or factories until the stage of mining activities requires a lot of labor. This is what is utilized by residents, especially farmers who have damaged or lost their land. Many people work in the company. The real impact of mining activities that occur in Kiaea Village is environmental damage, air pollution, rivers that were once clear are now murky or mixed with mud so that residents' rice fields are exposed to waste from mining, resulting in a lack of crop yields obtained by farmers and to overcome the problem, several strategies are needed. The strategies made are activating farmer groups, making boreholes, intensive maintenance or spraying, increasing fertilizer application, closing irrigation channels, working as mine laborers. These steps are new solutions to the problems faced and can maintain the rice fields.